2022
DOI: 10.1007/s10453-022-09759-2
|View full text |Cite
|
Sign up to set email alerts
|

Summer pollen flora in rural and urban central England dominated by nettle, ryegrass and other pollen missed by the national aerobiological network

Abstract: Abundance and diversity of airborne pollen are important to human health and biodiversity. The UK operational network collects airborne pollen from 8 flowering trees, grasses and three weeds using Hirst traps and microscopic identification from urban areas. Knowledge of total pollen diversity and differences between rural and urban zones is limited. We collect environmental DNA (eDNA) from air during summer and autumn over 3 years with mini cyclones from one urban and one rural site. Data are analysed using ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Many bioaerosols can be detected with DNA approaches, with examples covering pollen (e.g. Brennan et al, 2019), bacteria (Innocente et al, 2017) and fungal spores (Hanson et al 2022a(Hanson et al , 2022b. A recent review by Johnson et al (2023) discussed developments in botanical applications of airborne eDNA detection and highlighted the future potential for advancements in this area, such as monitoring species dispersal, population structures and conservation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many bioaerosols can be detected with DNA approaches, with examples covering pollen (e.g. Brennan et al, 2019), bacteria (Innocente et al, 2017) and fungal spores (Hanson et al 2022a(Hanson et al , 2022b. A recent review by Johnson et al (2023) discussed developments in botanical applications of airborne eDNA detection and highlighted the future potential for advancements in this area, such as monitoring species dispersal, population structures and conservation.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies on bioaerosols focus on specific periods such as transport of bacteria during spring (Abd Aziz et al, 2018), flowering of trees and plants (Adams-Groom et al, 2020) or sporulation and spore release during agricultural production periods (Hanson et al 2022a(Hanson et al , 2022bSkjøth et al, 2012). A consequence is that the bioaerosol composition outside of flowering periods or agricultural productive periods remains relatively unexplored, although studies such as Aalismail et al (2021) and Johnson et al (2021) have demonstrated the potential to advance understanding of plant ecology through monitoring atmospheric plant DNA, with possible relevance of long distance transport and detection of plant fragments, respectively.…”
Section: Introductionmentioning
confidence: 99%